PEMASARAN BARANG JADI BERBASIS KAYU EBONI DI PERUSAHAAN SUMBER URIP EBONI MELALUI ANALISIS SWOT - Darmawan, Nuraisyah; Umar, Syukur; Pribadi, Hendra (Universitas Tadulako, 2020)
AbstractThe furniture industry is one of the most highly valued timber industries in the world and absorbing labor, and then making significant contibutions to the economy of Â Indonesia. Eboni is a type of wood found in tropical areas such as Central Sulawesi. Eboni wood is usually used as a furniture, sculpture, decorative wall and plywood. Eboni wood in the market of Central Sulawesi is dominated in the form of furniture or souvemir. Eboni furniture or souvenir market has been exist mainly in Palu, the capital of Central Sulawesi. Unfortunately, the market demand has been decline over the last years. In this research, the method usedÂ was SWOT analysis to identify the perceived strengths and weaknesses and also opportunities and threats faced by the company. The result of research is indicate that Sumber Urip Eboni are quadrant 1 with the values of X-axis (1,62) and Y-axis (0,40), which means that companies can used the benefit from their strength and opportunity. The strategy to be applied in these conditions is to support aggressive growth polices.Keywords: Eboni, Furniture or Souvenir, and Marketing